Revealing the influence of Cyano in Anchoring Groups of Organic Dyes on Adsorption Stability and Photovoltaic Properties for Dye-Sensitized Solar Cells - Wei-Chieh Chen (Nature Portfolio, 2017)
Abstract Determining an ideal adsorption configuration for a dye on the semiconductor surface is an important task in improving the overall efficiency of dye-sensitized solar cells. Here, we present a detailed investigation of different adsorption configurations of designed model dyes on TiO2 anatase (101) surface using first principles methods. Particularly, we aimed to investigate the influence of cyano group in the anchoring part of dye on its adsorption stability and the overall photovoltaic properties such as open circuit voltage, electron injection ability to the surface. Our results indicate that the inclusion of cyano group increases the stability of adsorption only when it adsorbs via CN with the surface and it decreases the photovoltaic properties when it does not involve in binding. In addition, we also considered full dyes based on the results of model dyes and investigated the different strength of acceptor abilities on stability and electron injection ability. Among the various adsorption configurations considered here, the bidentate bridging mode (A3) is more appropriate one which has higher electron injection ability, larger VOC value and more importantly it has higher dye loading on the surface.